Subordinação e parassubordinação : a proteção dos direitos fundamentais sociais nas relações de trabalho contemporâneas - Azevedo, Flávio Alexandre Luciano de (2016)
The effectiveness of Labor Law is an important tool to promote human dignity and consequently for the protection of fundamental rights. From this perspective, there is the need of the frame analysis given to the employment relationship, because it depends on the degree of protection that will be applied to the employee. With the phase of the Labor Law crisis, which began in Europe in the 1970s, major portions of the productive sector discuss the need to reduce labor protection as the only way to make viable its economic activity. With a view to reducing labor costs, there are new forms of hiring workers, different from the employment relationship, such as labor unions, outsourcing, temporary work and the quasi subordination work. In this context, and with the development of productive processes, there is the necessity to revisit the identifying the employment relationship parameters. A line of scholars believes that currently the subordination is much attenuated in labor relations, because the production develop in sprayed manner and without there being any direct orders from the employee services taker. On the other hand, some scholars note that the profound changes in labor relations do not become less subordinate workers however that subordination is exercised by other ways facing the reproduction process engineering. Consequently, there are legislative innovations in some countries to regulate labor relations that are in grise zone between autonomy and subordination, highlighting the quasi subordination work. It is recorded that these workers have a degree of protection much lower than typical employees, given that many aspects defined by standard cogent in an employment relationship are left to the autonomy of contractual will of the parties in quasi subordination labor relations. To understand the appropriate institution of quasi subordination, it is important to understand that workers that are framed on it have a lower degree of disadvantage from the typical employees, because only in this way could be justify a less extensive labor protection. Therefore, the need for labor protection does not result from subordination in its classic design, but the disadvantage of a party of the working relationship over the other. That is why there is the need for a review of subordination, considering that in contemporary processes governing the power of the employer is exercised by means other than direct and constant emanation orders. The study of a broad conception of subordination leads us to understand the evolution of its concept and frame the workers who should actually be under the protection of labor laws in the typical work relationship, called the employment relationship.